New data on the morphology of Polygenis (Polygenis) rimatus (Jordan) (Siphonaptera: Rhopalopsyllidae) - Lareschi, Marcela (2005)
The study was carried out on the basis of 208 specimens of both sexes from a wide geographical range, from central Brazil to central Argentina. The morphology of diagnostic features of Polygenis (Polygenis) rimatus (Jordan) including the presence or absence of the ductus of the spermatheca with a thick wall, the shape of the posterior margin of seventh sternum in females, and the size of the angle between the distal and the proximal arms of the basal part of the aedeagal tubus, and the number of convolutions made by the coil of the aedeagal tubus interior in males, have been studied. The results obtained are important in clarifying some difficulty in species recognition. Besides, the variability of some characteristics between specimens from disjoint localities in Brazil and Argentina is also noticed.